Plasmon-pyroelectric nanostructures used to produce a temperature-mediated reactive oxygen species for hypoxic tumor therapy. (June 2021) - Chang, Yun; Cheng, Yan; Zheng, Runxiao; Wu, Xiaqing; Song, Panpan; Wang, Yanjing; Yan, Jiao; Zhang, Haiyuan
Highlights: Pyroelectric BaTiO3 (BTO) nanomaterials have a build-in electric field that can prevent the electron-hole recombination. Temperature variation on BTO nanomaterials facilitate the free hole release and O2 -independent hydroxyl radical generation. NIR laser irradiated plasmonic Au cores in Au@BTO CSNSs can heat pyroelectric BTO shell, leading to efficient ROS production. Biocompatible p Au@BTO CSNSs exhibit excellent in vitro and in vivo PDT and PTT performance for hypoxic tumor therapy. Graphical Abstract: ga1 Abstract: Photodynamic therapy (PDT) has attracted considerable attention for tumor treatment, however, its efficacy is dramatically limited by the low reactive oxygen species (ROS) generation efficiency at hypoxic tumor microenvironment. Herein, new plasmon-pyroelectric gold (Au)@barium titanate (BTO) core-shell (CS) nanostructures (NSs) were designed to produce a temperature-mediated oxygen (O2 )-independent PDT for hypoxic tumor therapy. Upon 808 nm laser irradiation, the plasmonic heating of Au cores was excited and transferred a heat to pyroelectric BTO shell, where the temperature elevation could decrease spontaneous polarization of BTO, leading to abundant hole released from the BTO surface and promoting to hydroxyl radical formation through an O2 -independent approach. Simultaneously, Au@BTO CSNSs still remain excellent photothermal performance originating from Au cores. Actually, 808 nm laser irradiated and polyethylene glycol modified Au@BTO CSNSs could exhibit promising phototherapeutic effects on 4T1 cells at hypoxic conditions and 4T1 tumor-bearing mice, showing great potential for hypoxic tumor therapy.